PENGARUH FLIPPED CLASSROOM BERBANTUAN MULTIMEDIA INTERAKTIF TER HADAP HASIL BELAJAR RANAH KOGNITIF SISWA DALAM PEMBELAJARAN AKUNTANSI - Naufal Dzaki Rifaldi; Sri Sumaryati; Binti Muchsini (Universitas Sebelas Maret, 2022)
ABSTRACT This study aims to examine the influence of interactive multimedia-assisted flipped classrooms on student cognitive learning outcomes in accounting learning. This study used a type of quasi experimental research with a pretest-postest control group design. The subjects of this study were students of class X financial and institutional accounting amount 71 students. The data collection techniques used are tests, observations, and documentation. Data analysis using Paired Sample T-Test to deter mine the improvement of student learning outcomes, Independent Sample T-Test to compare the learning outcomes of the con trol class and the experimental class, and the N-Gain to compare the degree of effectiveness of the learning outcomes of the control class and the experimental class. The results showed that there was a significant influence on the application of interac tive multimedia-assisted flipped classrooms on the learning outcomes of students' cognitive realms in accounting learning from the results of the Paired Sample T-Test test which showed a value of sig.0.000 with a significance level of 0.05. The results of the N-Gain test in the experimental class have a moderate level of effectiveness related to the influence of the application of interactive multimedia-assisted flipped classrooms with a value of 0.60. The conclusion of this study is that there is a signifi cant influence in the application of interactive multimedia-assisted flipped classrooms on the learning outcomes of the cognitive realm of students in accounting learning. Keywords: Flipped Classroom, Interactive Multimedia, Cognitive Realm ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh flipped classroom berbantuan multimedia interaktif terhadap hasil belajar ranah kognitif siswa dalam pembelajaran akuntansi. Penelitian ini menggunakan jenis penelitian eksperimen semu dengan desain pretest-postest control group design. Subjek penelitian ini adalah siswa kelas X Akuntansi Keuangan dan Lem baga yang berjumlah 71 siswa. Teknik pengumpulan data yang digunakan adalah tes, observasi, dan dokumentasi. Analisis data menggunakan Paired Sample T-Test untuk mengetahui peningkatan hasil belajar siswa, Independent Sample T-Test untuk mem bandingkan hasil belajar kelas kontrol dan kelas eksperimen, dan N-Gain untuk membandingkan tingkat keefektivitasan hasil belajar kelas kontrol dan kelas eksperimen. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan penerapan flipped classroom berbantuan multimedia interaktif terhadap hasil belajar ranah kognitif siswa dalam pembelajaran akuntansi dari hasil uji Paired Sample T-Test yang menunjukkan nilai sig.0,000 dengan tingkat signifikansi 0,05. Hasil uji N-Gain pada kelas eksperimen memiliki tingkat efektivitas sedang dalam kaitanya dengan pengaruh penerapan flipped classroom berbantuan multimedia interaktif dengan nilai 0,60. Kesimpulan penelitian ini yaitu terdapat pengaruh yang signifikan dalam penerapan flipped classroom berbantuan multimedia interaktif terhadap hasil belajar ranah kognitif siswa dalam pembelajaran akuntansi. Kata Kunci: Flipped Classroom, Multimedia Interaktif, Ranah Kognitif